Presentation Revista IEEE 16 (Journal of the Spanish Institute for Strategic Studies, 2021)
In preparing a new issue of the Spanish Institute of Strategic Studies Journal, we are particularly concerned that the articles should address issues of undoubted interest to Security, in its broadest sense, and at the same time provide novel approaches. And, on this occasion, it is so in an obvious way